TECHNOLOGY READINESS OF MADRASAH IBTIDAIYAH TEACHERS IN THE LEARNING PROCESS - Dian Hidayati; Nurhikmah; Shofia Noor Wachidatur Rochmah (Universitas Majalengka, 2023)
The readiness of teachers to use technology plays a vital role, so the use of learning technology must be designed as well as possible. Some problems occur when teachers are still not ready to use technology, and the use of the internet or technology has not been implemented optimally by teachers. Teacher readiness in teaching also needs to be improved, especially regarding learning technology to design subject matter to make it more attractive to improve the quality of education, which is the main agenda in improving the quality of MI (Madrasah Ibtidaiyah) to compete in the current era. global era. In addition, teachers must be more creative in learning and increase their readiness to utilize learning technology. However, not all schools can use technology due to limited infrastructure. The use of technology in schools will be optimal if equipped with adequate facilities so that students and teachers can access various learning resources. For this reason, this study aims to determine teacher readiness in using and utilizing learning technology to achieve learning goals in MI Pekat District, West Nusa Tenggara. This study used qualitative research methods. Data collection techniques include observation, interviews, and documentation. At the same time, processing data using qualitative methods systematically. technology The results of the study found that 1) there was teacher readiness in utilizing technology, but some teachers lacked knowledge about the use of technology, 2) the teacher's attitude towards the use of technology in learning was still not optimal, 3) lack of supporting facilities and infrastructure. From the results of this study, it can be concluded that it is crucial to analyze the technological readiness of teachers in utilizing learning technology, investigate attitudes toward using technology in learning, and examine the actual conditions in schools in utilizing technology. If this is analyzed and observed, the weaknesses and strengths regarding technological readiness in schools will be known, which will be used as a reference for future improvements. Kesiapan guru dalam menggunakan teknologi memegang peranan penting, sehingga pemanfaatan teknologi pembelajaran memang harus dirancang sebaik mungkin. Namun, terdapat guru yang belum siap dalam menggunakan teknologi. Kesiapan guru dalam mengajar menggunakan teknologi perlu ditingkatkan untuk merancang materi pelajaran agar lebih menarik untuk meningkatkan mutu pendidikan yang menjadi agenda utama dalam meningkatkan mutu MI (Madrasah Ibtidaiyah) untuk bersaing di era sekarang. Guru juga harus lebih kreatif dalam melaksanakan pembelajaran dan meningkatkan kesiapannya dalam memanfaatkan teknologi pembelajaran. Namun, tidak semua sekolah bisa menggunakan teknologi karena keterbatasan infrastruktur. Pemanfaatan teknologi di sekolah akan optimal jika dilengkapi dengan fasilitas yang memadai agar dapat digunakan untuk mengakses berbagai sumber belajar. Penelitian ini bertujuan untuk mengetahui kesiapan guru dalam memanfaatkan teknologi pembelajaran untuk mencapai tujuan pembelajaran di MI Kecamatan Pekat Nusa Tenggara Barat. Penelitian ini menggunakan metode penelitian kualitatif. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Data diolah menggunakan metode kualitatif secara sistematis. Hasil penelitian menemukan bahwa terdapat kesiapan guru dalam memanfaatkan teknologi, namun beberapa guru kurang memiliki pengetahuan dan sikap mengenai penggunaan teknologi yang belum optimal, kurangnya sarana yang mendukung. Jika menganalisis kesiapan teknologi, sikap guru, serta kondisi aktual, maka akan diketahui kekurangan dan kelebihan kesiapan teknologi di sekolah, sebagai acuan dalam perbaikan kedepannya.